Phonological acquisition process in hearing-impaired children: a systematic review - Jhanani S.Nagaraja; Badrulzaman Abdul Hamid; Nashrah Maamor (Penerbit Universiti Kebangsaan Malaysia, 2024)
Phonological acquisition processes are often associated with normal-hearing children. However, the phonological acquisition process in hearing-impaired children presents interesting challenges and variation in comparison to normal-hearing children. This systematic review aims to describe the phonological acquisition processes that hearing-impaired children underwent. An extensive literature search was carried out from March until May 2023 utilising three online database, which are Scopus, PubMed and JSTOR. Several studies such as cohort, case-control studies, and human cross-sectional studies, were chosen. From the 428 papers discovered, 32 studies were incorporated based on the inclusion and exclusion criteria. The inclusion criteria focused on research papers that involved children with hearing impairment in various degrees, aged between 0 to 12 years old, and interventions that included both cochlear implant and hearing aid users. The major exclusion criteria were studies with subjects with any syndromes and studies that analysed sign languages. The results indicated that final and initial consonant deletion, fronting, stopping, vowelization, substitution, reduplication and assimilation are the phonological acquisition processes that hearing-impaired children undergo. Furthermore, it was found that word or language difference is not a factor that affects the phonological acquisition process in hearing-impaired children. Lastly, final consonant deletion is a common phonological process that both normal and hearing-impaired children undergo at their early stages of hearing. This review aids in bringing awareness to speech language pathologist on the need for early and targeted intervention for hearing-impaired children to tackle the phonological acquisition process these children undergo.